MP36: Short-term side effects associated with opioids for acute pain. (May 2019) - Daoust, R.; Paquet, J.; Cournoyer, A.; Piette, E.; Morris, J.; Lessard, J.; Castonguay, V.; Lavigne, G.; Williamson, D.; Chauny, J.
Abstract : Introduction : Opioid side effects are common when treating chronic pain. However, the rate of opioid side effects for acute pain has rarely been examined, particularly in the post emergency department (ED) setting. The objective of this study was to evaluate the short-term incidence of opioid induced side effects (constipation, nausea/vomiting, dizziness, and drowsiness) in patients discharged from the ED with an opioid prescription.Methods : This was a prospective cohort study of patients aged ≥18 years that visited the ED for an acute pain condition (≤ 2 weeks) and were discharged with an opioid prescription. Patients completed a 14-day diary assessing daily pain medication use and side effects.Results : Mean age of the 386 patients included was 55 ± 16 years; 50% were women. During the 2-week follow-up, 80% of patients consumed at least one dose of opioids. Among the patients who used opioids, 38% (95%CI: 33-48) reported constipation, 27% (95%CI:22-32) nausea/vomiting, 30% (95%CI:25-35) dizziness, 51% (95%CI:45-57) drowsiness, and 77% (95%CI:72-82) reported any side effects. Adjusting for age, sex, and pain condition, patients who used opioids were more likely to report any side effect (OR 7.5, 95%CI:4.3-13.3) and constipation (OR 7.5, 95%CI:3.1-17.9). A significant dose response effect was observed for constipation but not for the other side effects. Nausea/vomiting (OR 2.0, 95%CI:1.1-3.6) and dizziness (OR 1.9, 95%CI:1.1-3.4) were associated with oxycodone compared to morphine.Conclusion : Similar to chronic pain, opioid side effects are highly prevalent during short-term treatment for acute pain. Physicians should be aware and inform patients about those side effects.